Viscous dissipation effect on amplitude and oscillating frequency of heat transfer and electromagnetic waves of magnetic driven fluid flow along the horizontal circular cylinder - Nidhal Ben Khedher; Zia Ullah; Y.M. Mahrous; Sami Dhahbi; Sohail Ahmad; Hanaa Abu-Zinadah; Abdullah A. Faqihi (Case Studies in Thermal Engineering, 2024)
The significant importance of present research is to remove the extreme temperature along the magnetic driven horizontal circular cylinder. The induced electromagnetic field is applied around the surface of cylinder. The main novelty of current research is to control thermal and magnetic boundary layer in the presence of viscous dissipation and induced electromagnetic field. The dimensional mathematical form is developed with defined boundary conditions. The dimensional equations are transformed into dimensionless equations to generate physical factors. The primitive form is used to reduce dimensionless equations into convenient form for smooth algorithm. The finite difference method with Gaussian elimination technique is applied for numerical results in FORTRAN language tool. The velocity, temperature and electromagnetic field are sketched graphically with asymptotic sequence. The oscillatory shear stress, oscillating heat rate and periodical current density is plotted graphically and numerically. It is found that fluid velocity improves significantly as buoyancy force increases around each position. It is noticed that the increasing oscillations in heat transfer are sketched for maximum choice of Prandtl number. It is found that the maximum oscillations in current density are obtained for each Eckert parameter. It is noticed that the significant distribution in temperature profile is obtained in the presence of viscous dissipation and magnetic field.